545 Recovery of post‐arthrodesis hand function in the interphalan‐ geal joint ‐ Case presentation (Balneo and PRM Research Journal, 2024)
Abstract: Objectives. The paper highlights the importance of the kinetic recovery program used toregain post‐arthrodesis hand function in the interphalangeal joint. Also, during the paper we willpresent both the techniques used and the methods applied in order to reduce pain and recover theremaining functional.Keywords: hand, fracture, arthrodesis, recovery, gaming sistem